Contingency Ranking and Screening of an IEEE Bus-6 Case System with Distributed Generation - Christopher T. Adina, John; Mark L. Gonzales, John; John C., Jonathan; Patrick L. Fontanilla, Julius; C. Pacis, Michael; E. Chua, Esperanza (International Journal of Engineering and Technology, 2018)
Power System is a large system that is very sensitive to damage and failure especially in line and power outages, to assess the system security, contingency analysis allows systems to be operated. Many problems that occur on a power system cause serious trouble if not accounted and must be solved quickly. The objective is to create a program on how to have a quicker response on every contingencies. To solve this problem, the researchers had developed an algorithm for ranking and screening the contingencies for every line and power outages of an IEEE 6-Bus case system. Newton Raphson Load Flow (NRLF) was used to determine the line contingencies in the system and Performance Index (PI) ranked the contingencies based on their severity. The researchers were able to make a contingency analysis with a time of at least 10 minutes for computation.Â